Pemasaran Digital dalam Perspektif Akademis: Studi Bibliometrik Literatur Global - Feizal Septya Pradana Izal; Tony Wijaya; Agung Utama (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to examine the development and structure of academic literature on digital marketing through a bibliometric analysis approach. Digital marketing has become a central topic in marketing studies, especially since the COVID-19 pandemic, which has accelerated the adoption of digital technology across various sectors. Methodology: Data were collected from the Scopus database covering the period 2005–2025, identifying 111 documents containing the keywords “digital marketing” and “e-marketing” in the title, abstract, and keywords. VOSviewer software was employed to perform mapping of thematic networks, visualization of temporal trends, and analysis of literature density. Results: The findings reveal that the dominant research themes focus on social media marketing, purchase intention, content marketing, and the integration of advanced technologies such as artificial intelligence (AI), big data analytics, and chatbots. The visualization indicates a significant shift from traditional marketing discussions toward more technology-driven and behaviorally adaptive topics. Conclusions: Digital marketing research has evolved dynamically, moving toward more data-based and technology-oriented themes that reflect contemporary consumer trends. Limitation: This study is limited to publications indexed in Scopus and may exclude relevant works from other academic databases or gray literature. Contribution: The study contributes to a systematic understanding of the intellectual structure and thematic evolution of digital marketing research, offering valuable insights for academics and practitioners to identify research gaps and future directions in technology-based marketing studies.